Karakteristik Spasial - Fungsional Ruang Terbuka Hijau Taman Olahraga-Rekreasi dan Taman Bermain Anak Pada Taman Trunojoyo Kota Malang - Muhammad Satya Adhitama; Lisa Dwi Wulandari; Damayanti Asikin; Sigmawan Tri Pamungkas (RUAS, 2023)
The existence of public space is an indication of good urban spatial planning. Activities in green open spaces are a simple way to improve mental and physical health. In post-pandemic conditions, people's preference for choosing public spaces, especially green open spaces as places for activities, socializing, or cheap recreation in the city center, has decreased. Therefore, a study was conducted to see the quality and characteristics of green open spaces which are the preferences of the people of Malang City in carrying out activities in these spaces. The research focuses on two types of green open spaces, namely sports recreation parks and children's playgrounds located in Trunojoyo Park, Malang City. This research uses a rationalistic study approach, with primary data from observations and interviews and secondary data through an assessment of 10 success criteria for public spaces according to Carmona (2019), namely evolving, diverse, free, delineated, engaging, meaningful, social, balanced, comfortable, robust. The study result shows that people's preferences in choosing green open spaces are the completeness and condition of the facilities in them